Design of an Enterprise Network Terminal Security Solution - Muhammad Idris Abubakar; Ajayi Ore-Ofe; Abubakar Umar; Ibrahim Ibrahim; Lawal Abdulwahab Olugbenga; Ajikanle Abdulbasit Abiola (Vokasi UNESA Bulletin of Engineering, Technology and Applied Science, 2025)
This paper presents a secure enterprise network terminal security solution designed to protect the confidentiality, integrity, and availability of critical data and network resources. It presents a logical approach to creating an enterprise network security architecture with a primary focus on optimizing and enhancing the performance of as data center servers and storage. Traditionally, network infrastructure has primarily focused security measures on core components, such as firewalls and intrusion detection/prevention systems (IDS/IPS). However, the exponential growth of Internet of Things (IoT) devices, Bring Your Device (BYOD) policies, and remote workforce trends has shifted the threat landscape, making network terminals key vectors for malicious access, with critical end devices often being the ultimate targets. This study presents a comprehensive framework that prioritizes terminal-level security by integrating existing encryption techniques, specifically a double layer VPN tunnel architecture, to enhance data transmission confidentiality. A significant contribution of the paper lies in its structured classification of network terminals into thoughtful, intelligent, and dumb categories based on capability and memory—an approach that supports tailored securityimplementations. The framework also outlines contingency measures for securing data center endpoints in the event of a breach scenario. The novelty of this work lies in its focused protection strategy for terminals within enterprise environments, bridging the security gap between endpoints and core infrastructure. The proposed solution demonstrates the potential to reduce exposure to ransomware and targeted attacks through layered defenses and a proactive disaster recovery and business continuity (DR&B) strategy, despite limitations in real-world simulation due to resource constraints.